Critical Approach in the Transmission of al-Syaibānī’s Version of al-Muwatta Mālik in Iraq - M. Shofiyyuddin; Machasin; Jafar Assagaf (Millati: Journal of Islamic Studies and Humanities, 2025)
This paper investigates al-Syaibānī’s transmission activities on Mālik’s al-Muwaṭṭa`. Investigating al-Syaibānī’s transmission on Mālik’s al-Muwaṭṭa` provides an alternative discourse on the motivation of al-Syaibānī’s transmission on al-Muwaṭṭa` where he was part of the Iraqi jurisprudential community. al-Muwaṭṭā` is a representation of the legal material that represents the legal community in Medina. This research was conducted by textually comparing al-Syaibānī’s version of al-Muwaṭṭa` circulating in Iraq with two versions of Mālik’s followers living in Medina and al-Andalūs, namely, Abū Muṣ’ab and Yaḥyā al-Laiṡī. The text is then analyzed for its response, commentary and the composition of al-Syaibānī’s al-Muwaṭṭa`. The result of this study found that al-Syaibānī’s narration activity of al-Muwaṭṭa` illustrates critical transmission; al-Syaibānī compared al-Muwaṭṭa’s authoritative tradition from Medina with the Iraqi tradition that al-Syaibānī followed. al-Syaibānī, in this comparison, of course used argumentative material, from within the tradition he followed, whose authority was equal to or higher than al-Muwaṭṭa’s authority. Al-Syaibānī took the text of al-Muwaṭṭa` as authoritative to argue legitimacy for the practice of al-Syaibānī’s community in Iraq. The last point is that al-Syaibānī transmitted al-Muwaṭṭa`, instead of following the text, he opposed the ruling in the text. He took and brought in a text that had a higher authority than that of al-Muwaṭṭa’Mālik, even though the text did not come from Kufa but from Basra.